1957
DOI: 10.1039/jr9570001556
|View full text |Cite
|
Sign up to set email alerts
|

299. Cyclisation of some thiobenzamido-compounds

Abstract: Lawsout autd Searle: 299. Cyclisation of Some T h i o b e n z a r n i d o -c u d . By ALEXANDER LAWSON and C. E. SEARLE. N-Thiobenzoylsarcosie and N-ethyl-N-thiobenzoylglycine undergo ring closure in hot acid anhydrides, to give meso-ionic compounds (IV). Thiobenzamidoacetaldehyde diethyl acetal has been cyclised to the ethoxythiazoline (VI) and the thiazole (VII). Thiobenzoyl-semicarbazide and -thiosemicarbazide are cyclised to the hydroxy-(IX) or mercapto-thiadiazole (XII) or the aminothiadiazole (X) , depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1959
1959
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Recent work has shown that the electron-donor properties of N-heterocyclic carbene ligands [9] substantially increase when the heteroatoms of the ring are positioned at remote positions. [10] For example, mesoionic [11] 1,2,3-triazol-5-ylidenes (B, Figure 1) bear only one nitrogen adjacent to Abstract: A series of PEPPSI-type palladium(II) complexes was synthesized that contain 3-chloropyridine as an easily removable ligand and a triazolylidene as a strongly donating mesoionic spectator ligand. Catalytic tests in Suzuki-Miyaura cross-coupling re-A C H T U N G T R E N N U N G actions revealed the activity of these complexes towards aryl bromides and aryl chlorides at moderate temperatures (50 8C).…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has shown that the electron-donor properties of N-heterocyclic carbene ligands [9] substantially increase when the heteroatoms of the ring are positioned at remote positions. [10] For example, mesoionic [11] 1,2,3-triazol-5-ylidenes (B, Figure 1) bear only one nitrogen adjacent to Abstract: A series of PEPPSI-type palladium(II) complexes was synthesized that contain 3-chloropyridine as an easily removable ligand and a triazolylidene as a strongly donating mesoionic spectator ligand. Catalytic tests in Suzuki-Miyaura cross-coupling re-A C H T U N G T R E N N U N G actions revealed the activity of these complexes towards aryl bromides and aryl chlorides at moderate temperatures (50 8C).…”
Section: Introductionmentioning
confidence: 99%
“…167-169 "C; 1.25-1.40 g, 65-72%). Crystallisation by dissolution in a large volume of acetone (4 x 50 ml per g) and vacuum evaporation of the filtered liquid (to half-volume or less) gave opaque deep-yellow microcrystalline (16a), m.p. 166-168 "C (decomp.)…”
Section: Bis(c-phenyl-n-ureidoyormimidoyl Disulphide (16a)-(a)mentioning
confidence: 99%
“…PhCONH2,21' PhCONMe2,21b tico, 170. 4 . The fully heteroaromatic nature and consequent enhanced resonance stabilisation of the latter is a factor likely to contribute to this difference.…”
mentioning
confidence: 99%
“…This reaction has been successfully applied to other DNP-amino acids including DNIP-sarcosine and DNP-proline. The fact that these derivatives decarboxylate readily indicates that a cyclic intermediate, either of the type proposed by Cornforth & Elliott (1950) or by Lawson & Searle (1957), may not be essential for this decarboxylation as these amino acid derivatives contain tertiary aminogroups.…”
Section: Proceedings Of the Biochemical Society A Study Of The Mechanmentioning
confidence: 99%